2013
DOI: 10.6061/clinics/2013(02)oa03
|View full text |Cite
|
Sign up to set email alerts
|

Passive body heating improves sleep patterns in female patients with fibromyalgia

Abstract: OBJECTIVE:To assess the effect of passive body heating on the sleep patterns of patients with fibromyalgia.METHODS:Six menopausal women diagnosed with fibromyalgia according to the criteria determined by the American College of Rheumatology were included. All women underwent passive immersion in a warm bath at a temperature of 36±1°C for 15 sessions of 30 minutes each over a period of three weeks. Their sleep patterns were assessed by polysomnography at the following time-points: pre-intervention (baseline), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…Local skin warming in the foot or hand was not reported to be associated with an increase in the core body or skin temperature of other parts of the targeted region 22,23 . Furthermore, whole passive body warming was documented to increase both the core body and skin temperatures 7,24 . Only one study has demonstrated a skin temperature increase in the feet and hands after local skin warming in the abdominal or lumbar region 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Local skin warming in the foot or hand was not reported to be associated with an increase in the core body or skin temperature of other parts of the targeted region 22,23 . Furthermore, whole passive body warming was documented to increase both the core body and skin temperatures 7,24 . Only one study has demonstrated a skin temperature increase in the feet and hands after local skin warming in the abdominal or lumbar region 20 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on the effects of passive body heating on subjective and objective sleep. Studies using a variety of bathing conditions have suggested that bathing at an appropriate temperature (41 ± 0.5 °C) for 30 min before bedtime improves subjective sleep and increases slow wave sleep in the first sleep cycle [ 9 , 10 ]. Both subjective and objective changes after passive body heating are likely to be related to sleep consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…As a physiological intervention, bathing at an appropriate temperature and with optimal timing has been reportedly associated with a subjective improvement of sleep initiation and an objective increase in deep EEG sleep, possibly due to general relaxation and/or increased heat loss after such warming interventions [ 8 10 ]. Warming of the hand or foot skin before bedtime has been reported to improve sleep quality and decrease core body temperature in elderly subjects with or without insomnia [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] It is an ancient way to treat rheumatic and musculoskeletal disorders which can relieve the pain and improve the function in musculoskeletal disorders, [2326] but the mechanism has not been clearly illuminated. [27,28] It may associate with hydrostatic pressure, mineral composition, and temperature. [23,29,30] Immersing in warm water may contribute to an analgesic effect by thermal effect and hydrostatic pressure of water on the skin according to the “Gate control theory of pain.” [31] And due to a lower specific heat, mud-pack therapy elevates the body-core temperature more efficiently.…”
Section: Introductionmentioning
confidence: 99%